2020
DOI: 10.1128/jvi.01985-19
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Innate Immunity Transcriptomes from Spodoptera frugiperda Larvae Infected with the Spodoptera frugiperda Ascovirus

Abstract: Ascoviruses are large, enveloped DNA viruses that induce remarkable changes in cellular architecture during which the cell is partitioned into numerous vesicles for viral replication. Previous studies have shown that these vesicles arise from a process resembling apoptosis yet which differs after nuclear lysis in that mitochondria are not degraded but are modified by the virus, changing in size, shape, and motility. Moreover, infection does not provoke an obvious innate immune response. Thus, we used in vivo R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…However, it remains unknown how replication continues after their caspase and similar proteins cause nuclear lysis 17 , 18 . Since ascoviruses cause a chronic disease that lasts for weeks, we expanded our previous in vivo transcriptomic studies 22 , 26 by extending our SfAV experiments to three weeks and making these comparative by including TnAV. We compared hemolymph transcriptomes at 7, 14, and 21 days for both viruses with those of the other primary body tissues at the same time points.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unknown how replication continues after their caspase and similar proteins cause nuclear lysis 17 , 18 . Since ascoviruses cause a chronic disease that lasts for weeks, we expanded our previous in vivo transcriptomic studies 22 , 26 by extending our SfAV experiments to three weeks and making these comparative by including TnAV. We compared hemolymph transcriptomes at 7, 14, and 21 days for both viruses with those of the other primary body tissues at the same time points.…”
Section: Discussionmentioning
confidence: 99%
“…'asco' in Greek meaning 'sac' . Ultrastructural and more recent transcriptome studies indicate that ascoviruses manipulate host-cell mitochondria to provide the energy required for synthesizing the membranes that delimit viral vesicles [2,10,11]. After formation, these vesicles accumulate in the larval haemolymph, turning it milky white and continue to assemble progeny virions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous transcriptome studies on ascoviruses found that as the infection progresses there are significant expression variations in viral and lepidopteran host genes [10][11][12][13]. All of these studies were conducted in vivo due to a lack of a robust in vitro tissue culture system for ascovirus replication that closely resembles cell pathogenesis in larvae [14].…”
Section: Introductionmentioning
confidence: 99%
“…The HvAV‐3h‐infected larvae showed reduced feeding, stunted growth, and extended lifespan (S. J. Li et al, 2013, 2016; Yu et al, 2018). A previous study showed that infection by Spodoptera frugiperda ascovirus (SfAV‐1a) moderated the host immune response of S. frugiperda larvae and prolonged the larval developmental period by increasing certain negative regulators of Tolls, melanization, and phagocytosis pathways (Zaghloul et al, 2020). Ascovirus‐infected insect cell lines stopped proliferating (Asgari, 2006; Federici & Govindarajan, 1990; Govindarajan & Federici, 1990; Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, 2013Li et al, , 2016Yu et al, 2018). A previous study showed that infection by Spodoptera frugiperda ascovirus (SfAV-1a) moderated the host immune response of S. frugiperda larvae and prolonged the larval developmental period by increasing certain negative regulators of Tolls, melanization, and phagocytosis pathways (Zaghloul et al, 2020).…”
mentioning
confidence: 99%